Le Laboratoire de paysage d’Alnarp en Suède : une expérience de « gestion créative » - Catherine Szanto (Projets de Paysage)
At the Alnarp campus in Sweden, Professor Roland Gustavsson has developed an experimental forestry plantation called a “Landscape Laboratory”. He uses it to explore different forest management methods by seeking in each specific form the aspects which may satisfy the requirements of foresters or ecologists while providing visitors with a rich and diverse experience. The originality of the laboratory lies in the fact that it integrates the dimension of the landscape in the experiment, in other words, it enables the study of the spatial qualities in different forest structures and the modalities of the spatial experiences they are able to provide. The research is based on observation, through drawings and measurements, but also on action (“creative management”): the forest is accompanied in its evolution by the traditional gestures of the foresters who provide original forest spaces, thus offering an alternative to a normalisation of the landscape.